2016
DOI: 10.1371/journal.pone.0146461
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Impacts of Tropical Forest Fragmentation on Arthropod Biodiversity and on their Patterns of Interactions with Host Plants

Abstract: Tropical rain forest fragmentation affects biotic interactions in distinct ways. Little is known, however, about how fragmentation affects animal trophic guilds and their patterns of interactions with host plants. In this study, we analyzed changes in biotic interactions in forest fragments by using a multitrophic approach. For this, we classified arthropods associated with Heliconia aurantiaca herbs into broad trophic guilds (omnivores, herbivores and predators) and assessed the topological structure of intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 47 publications
1
26
1
2
Order By: Relevance
“…As the number of bracts increased in the inflorescences, abundance and richness also tended to increase. This change in the colonizing fauna has been reported previously (Seifert 1982;Richardson & Hull 2000;Garcia-Robledo et al 2005;Yee & Willig 2007) and recently, Benítez-Malvido et al (2016) have shown the influence of the fragmentation of the tropical forest on the phytotelmata arthropod biodiversity in Heliconia bracts. The habitat affects species abundance, and the diversity and composition were higher in continuous forest (Benítez-Malvido et al 2016).…”
Section: Discussionsupporting
confidence: 79%
“…As the number of bracts increased in the inflorescences, abundance and richness also tended to increase. This change in the colonizing fauna has been reported previously (Seifert 1982;Richardson & Hull 2000;Garcia-Robledo et al 2005;Yee & Willig 2007) and recently, Benítez-Malvido et al (2016) have shown the influence of the fragmentation of the tropical forest on the phytotelmata arthropod biodiversity in Heliconia bracts. The habitat affects species abundance, and the diversity and composition were higher in continuous forest (Benítez-Malvido et al 2016).…”
Section: Discussionsupporting
confidence: 79%
“…Farneda et al (2015) showed that diet type is an important predictor of vulnerability to fragmentation in phyllostomids, and this may also be true for AIB. In fact, insectivorous bats have distinct diets that include a broad diversity of insect groups or adjust their activity patterns to new environmental conditions (Kalka and Kalko, 2006;Lawer and Darkoh, 2016;Kemp et al, 2019;Rocha et al, 2019) and there is evidence that some of these are substantially impacted by forest fragmentation (Didham et al, 1996;Golden and Crist, 1999;Rösch et al, 2013;Benítez-Malvido et al, 2016). Diet type may thus influence the vulnerability of AIB to fragmentation, but we could not include this trait in our study due to the scarcity of knowledge about the diet of the species involved.…”
Section: Caveats and Future Research Directionsmentioning
confidence: 99%
“…Forest edges are the point of entry for external influences, including the invasion of native and exotic species, and so, facilitate novel and/or opportunistic host–herbivore and host–pathogen associations (Benítez‐Malvido, ; Benítez‐Malvido et al., ; Benítez‐Malvido & Lemus‐Albor, ; Gilbert & Hubbell, ). This is because, soon after edge creation, forest structure, plant species abundance, and composition, as well as the physical and biological environments in the forest canopy and understory, are strongly modified (Gilbert & Hubbell, ; Laurance et al., , , ).…”
Section: Introductionmentioning
confidence: 99%